AM1* parameters for cobalt and nickel - Kayi, Hakan; Clark, Timothy (Journal of Molecular Modeling, 2010)
We report the parameterization of AM1* for the elements Co and Ni. The basis sets for both metals contain one set each of s-, p- and d-orbitals. AM1* parameters are now available for H, C, N, O and F (which use the original AM1 parameters), Al, Si, P, S, Cl, Ti, V, Cr, Co, Ni, Cu, Zn, Br, Zr, Mo and I. The performance and typical errors of AM1* are discussed for Co and Ni and compared with available NDDO Hamiltonians.